GIEE 2011 : Formation Interdisciplinaire des Ingénieurs et Problème du Genre. - Béraud, André (Springer, 2012)
Attracting more young people, particularly women, in Engineering and Technology (ET) is a major concern in Europe today. Their participation in engineering occupations appears to be a key-issue for European economic and technical development, as well as a central achievement towards gender equality and social justice. Increasing young people's interest in the sciences and mathematics and underlining the importance of Engineering and Technology developments in shaping our collective future is an ongoing project in the education sector. This book presents various analyses and ideas for possible.